Comparison of diverse developmental transcriptomes reveals that coexpression of gene neighbors is not evolutionarily conserved - Yanai, Itai; Hunter, Craig P. (Genome Research, 2009)
Genomic analyses have shown that adjacent genes are often coexpressed. However, it remains unclear whether the observed coexpression is a result of functional organization or a consequence of adjacent active chromatin or transcriptional read-through, which may be free of selective biases. Here, we compare temporal expression profiles of one-to-one orthologs in conserved or divergent genomic positions in two genetically distant nematode species—Caenorhabditis elegans and C. briggsae—that share a near-identical developmental program. We find, for all major patterns of temporal expression, a substantive amount of gene expression divergence. However, this divergence is not random: Genes that function in essential developmental processes show less divergence than genes whose functions are not required for viability. Coexpression of gene neighbors in either species is highly divergent in the other, in particular when the neighborhood is not conserved. Interestingly, essential genes appear to maintain their expression profiles despite changes in neighborhoods suggesting exposure to stronger selection. Our results suggest that a significant fraction of the coexpression observed among gene neighbors may be accounted for by neutral processes, and further that these may be distinguished by comparative gene expression analyses.
10.1101/gr.093815.109